2003
DOI: 10.1021/ja0358697
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)-Catalyzed Selective Intramolecular [2 + 2 + 2] Alkyne Cyclotrimerizations

Abstract: In the presence of a catalytic amount of Cp*RuCl(cod), 1,6-diynes chemoselectively reacted with monoalkynes at ambient temperature to afford the desired bicyclic benzene derivatives in good yields. A wide variety of diynes and monoynes containing functional groups such as ester, ketone, nitrile, amine, alcohol, sulfide, etc. can be used for the present ruthenium catalysis. The most significant advantage of this protocol is that the cycloaddition of unsymmetrical 1,6-diynes with one internal alkyne moiety regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
203
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(218 citation statements)
references
References 87 publications
12
203
0
3
Order By: Relevance
“…of 3-hexyne with an Ru catalyst gave only 13 % of the desired product. [7] Very recently, Takeuchi and co-workers recommended a slow addition technique for such reactions to minimize the self-addition of the diyne: thus, they employed an [Ir-A C H T U N G T R E N N U N G (cod)Cl] 2 /dppe catalyst for the cyclotrimerization using the procedure of slow addition (7 h) of diyne to the mixture of monoyne (3 equivs.) and catalyst to provide the corresponding benzene derivative in good yield.…”
Section: Resultsmentioning
confidence: 99%
“…of 3-hexyne with an Ru catalyst gave only 13 % of the desired product. [7] Very recently, Takeuchi and co-workers recommended a slow addition technique for such reactions to minimize the self-addition of the diyne: thus, they employed an [Ir-A C H T U N G T R E N N U N G (cod)Cl] 2 /dppe catalyst for the cyclotrimerization using the procedure of slow addition (7 h) of diyne to the mixture of monoyne (3 equivs.) and catalyst to provide the corresponding benzene derivative in good yield.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] In many cases, arene-type ligands have been employed as electron-donors to stabilize the metal charge. 19b, [22][23][24] We added electron-rich arenes in the reaction medium to test a possible enhancement of the cyclotrimerization reaction and the results in Figure 2 show that Au supported-solids become in general more active for the cyclotrimerization of 1 in the presence of methoxy-substituted arenes.…”
Section: -Reaction Mechanismmentioning
confidence: 99%
“…14 ). We observed that [2+2+2] cycloaddition of dimethyl acetylenedicarboxylate (2) using catalyst 1 (1 mole %) 15 was not only air-tolerant 16 but also proceeded in presence of water without any added organic co-solvent (Scheme 1, 17 . Under these mild aerobic conditions, the starting material was consumed within 5.5 h and hexamethyl mellitate 3 was isolated in 76% yield.…”
Section: Resultsmentioning
confidence: 99%